Effects of Dietary Levels of Energy and Protein at the Finishing Stage. 1. Performance and Pelt Production of Rex Rabbits - A. Habibie; D. Kusnidar; T. Sartika; Y. C. Raharjo (Buletin Peternakan, 1995)
Abstrak dalam bentuk hard copy